ANALISIS PERTUMBUHAN PDRB SEKTOR PERTANIAN DI KABUPATEN PADANG PARIAMAN: IMPLIKASI PERUBAHAN IKLIM TERHADAP KELOMPOK RENTAN - Suci Kurnia Sari; Henny Puspita Sari (Ekasakti Jurnal Penelitian dan Pengabdian)
This study analyzes the growth of the agricultural sector's Gross Regional Domestic Product (GRDP) in Padang Pariaman Regency and examines the implications of climate change on vulnerable groups. The research utilizes secondary data from 2013 to 2022, employing Location Quotient (LQ) and Dynamic Location Quotient (DLQ) analyses. Results indicate that while the agricultural sector remains a significant contributor to GRDP, it faces challenges due to climate change, such as erratic weather patterns and reduced productivity. Vulnerable groups, particularly smallholder farmers, are disproportionately affected, necessitating adaptive strategies and supportive policies.